2019
DOI: 10.1002/cpt.1315
|View full text |Cite
|
Sign up to set email alerts
|

The Confluence of Accelerated Regulatory and Health Technology Assessment Access Pathways

Abstract: There is a growing interest in aligning accelerated regulatory pathways with flexible access and reimbursement pathways to expedite the equitable availability of high-quality, safe, and effective medicines that provide a valuebased approach to meeting society's most important healthcare needs. The Centre for Innovation in Regulatory Science (CIRS) identified key issues regarding the confluence of regulatory and health technology assessment processes from discussions and presentations given by international reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 14 publications
0
10
0
4
Order By: Relevance
“…Such trust is key both from patients to understand the decisionmaking process, as well as from other stakeholders particularly in the case of agencies aligning their decision-making processes. 5,6 In addition, the routine assessment of the QDMPs has the ability to measure change over time in order to determine the impact of any improvement initiatives. The ongoing use of quality frameworks for making decisions will also reduce uncertainty around decision-making and might result in more predictable and favourable outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such trust is key both from patients to understand the decisionmaking process, as well as from other stakeholders particularly in the case of agencies aligning their decision-making processes. 5,6 In addition, the routine assessment of the QDMPs has the ability to measure change over time in order to determine the impact of any improvement initiatives. The ongoing use of quality frameworks for making decisions will also reduce uncertainty around decision-making and might result in more predictable and favourable outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…This applies to both how individuals decisions on a daily basis, as well as how key strategic decisions are made across a range of organisations including the pharmaceutical industry. 6 A recent review of the literature identified general paucity of research in this area, particularly regarding the development and systematic application of techniques for evaluating quality decision-making, such as through the studies undertaken as part of this research. 9 Indeed this is the first assessment to evaluate quality of decision-making within the different organisations involved in the development, review and reimbursement of medicines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The company perception may be as a result of high uncertainty around the effectiveness of such treatments that HTA agencies and payers may be concerned to accept [18,19]. This also highlights the need to better align accelerated regulatory pathways with flexible access and reimbursement pathways to expedite the equitable availability of high-quality, safe, and effective medicines that provide a value-based approach to meeting society's most important healthcare needs [20].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are concerns that the role of HTA agencies as final gatekeepers may be compromised through early involvement with developers. However, according to McAuslane et al, if the current challenges with early dialogue are properly addressed, it "is the process that will likely provide the greatest return on investment of time and effort to identify, develop, review, and recommend important new medicines, especially those that address an unmet medical need" (67).…”
Section: Tripartite Early Dialoguesmentioning
confidence: 99%